1968
DOI: 10.1111/j.1348-0421.1968.tb00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement Requirement of the Neutralizing Antibody Appearing After Immunization with Smallpox Vaccine

Abstract: A sensitive solid phase radioimmunoassay method was established for the specific quantitative determination of secretory IgA (sIgA) by taking advantage of the dual antigenicities of sIgA, one specific for α‐chain and the other for secretory component (SC). The sIgA and IgA in the sample were first bound by anti‐IgA antibodies coated on the polystyrene tube, then the amount of bound sIgA was quantified by the use of 125I‐labeled anti‐SC antibodies. This method is quite sensitive and allows us to distinguish sIg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

1971
1971
1974
1974

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 3 publications
1
17
0
Order By: Relevance
“…In the case of herpes virus, early CRN antibody frequently far exceeds N antibody in level and, as a consequence, enhancement by C' of the neutralizing activity of such a serum is almost of the all-or-none type. A similar fact has been noted with vaccinia [23], bovine parainfluenza [17] and simian her-pes SA 8 viruses [29]. For other viruses, occurrence of a similar response either remains undetermined or is denied [11].…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…In the case of herpes virus, early CRN antibody frequently far exceeds N antibody in level and, as a consequence, enhancement by C' of the neutralizing activity of such a serum is almost of the all-or-none type. A similar fact has been noted with vaccinia [23], bovine parainfluenza [17] and simian her-pes SA 8 viruses [29]. For other viruses, occurrence of a similar response either remains undetermined or is denied [11].…”
mentioning
confidence: 66%
“…The present results have indicated that the all-or-none type of C' enhancement of early neutralizing antibody as observed in the case of herpes simplex [9,[40][41][42] and some other viruses [17,23,29] cannot be seen in the immunization of rabbits or guinea pigs with WEE virus. The fact that the 2 species of animals tested exhibited a similar response to the immunization, as well as the failure of the rabbit antiserum to neutralize the closely related Sindbis virus, may deny the possibility that a hitherto unknown virus, which is antigenically closely related to WEE virus, had previously infected the animals and caused a secondary response upon the immunization with WEE virus.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The effect of C' was especially marked with early serum against relatively large viruses such as herpes [9,31,32], simian herpes [21] or vaccinia [17]. In the case of cytomegalovirus, early and late IgG were equally enhanced by C' [8].…”
mentioning
confidence: 99%